Gendered health impacts of industrial gold mining in northwestern Tanzania: Perceptions of local communities - Merten, Sonja; Kihwele, Andrea; Lyatuua, Fadhila; Kengiad, Isaa; James T; Winklera, Andrea; Mirko S; Merten, Sonja (Impact assessment and project appraisal journal, 2024)
A research article submitted to the Impact assessment and project appraisal journal Vol. 39.No. 3 of 2021